2020
DOI: 10.1002/jqs.3262
|View full text |Cite
|
Sign up to set email alerts
|

A bio‐available strontium isoscape for eastern Beringia: a tool for tracking landscape use of Pleistocene megafauna

Abstract: Numerous paleoecological questions concern the mobility of ancient fauna in eastern Beringia. Strontium (Sr) isotope ratio (87 Sr/ 86 Sr) analysis has emerged as a powerful tracer for determining the provenance of ancient biological materials. However, it is important to characterize 87 Sr/ 86 Sr variation across a landscape. We measured the 87 Sr/ 86 Sr composition of teeth from present-day, herbivorous rodents (n = 162) sampled from across eastern Beringia to estimate bio-available 87 Sr/ 86 Sr values. We co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 86 publications
(154 reference statements)
0
13
0
Order By: Relevance
“…Isotopes have gained popularity for reconstructing the mobility of now-dead individuals or extinct animals in archaeology and paleoecology [1][2][3][4][5]. Isotopes are ubiquitous in organic tissues and vary predictably in the environment with biological and physical processes [6].…”
Section: Introductionmentioning
confidence: 99%
“…Isotopes have gained popularity for reconstructing the mobility of now-dead individuals or extinct animals in archaeology and paleoecology [1][2][3][4][5]. Isotopes are ubiquitous in organic tissues and vary predictably in the environment with biological and physical processes [6].…”
Section: Introductionmentioning
confidence: 99%
“…Despite a variety of methodological approaches for examining niche partitioning and assessing the complex trophic relationships, geographical trends between members of the same species, remain difficult to assess due to the high degree of similarity in isotopic ratio values. The present research attempts to address this not totally neglected topic 61 , 62 and methodological gap 11 . Regardless of whether isotope data were derived from badger hair samples potentially including data from more than one badger, or samples where genotyping was used to account for individuals, linear regression analyses indicated that specific isotopic ratio values were associated with different land classes.…”
Section: Discussionmentioning
confidence: 99%
“…One rapidly growing area of strontium isotope research, especially over the last 5 years, has been the advancement and use of computational approaches both to develop and refine strontium isoscapes (e.g., Bataille et al, 2018Bataille et al, , 2020Funck et al, 2021;Holt et al, 2021). The methodological considerations of isoscape mapping, especially in terms of appropriate data and sample selection, have been the subject of a number of recent papers.…”
Section: Recent Advances In Isoscape Mapping and Spatial Assignmentmentioning
confidence: 99%
“…The benefit of multi-isotope research is not new, but researchers are only beginning to combine multiple isotopes in isoscape mapping and spatial assignments (see Bataille et al, 2021 for an example and discussion). Depending on what underpins spatial variability in other isotope systems (e.g., geology, anthropogenic emissions, and coastal proximity for sulfur, or climate and topography for oxygen or hydrogen), multi-isotope approaches can reinforce (or alternatively, challenge) inferences made from strontium isotopes alone (e.g., Leach et al, 2009;Crowley et al, in press;Czére et al, in press;Neil et al, 2020;Colleter et al, 2021;Funck et al, 2021;Reich et al, 2021;Wooller et al, 2021). Trace element studies, such as those using lead, can also provide more nuanced insights (e.g., Shaw et al, 2016;Moore et al, 2020;Walser et al, 2020).…”
Section: Importance Of Multi-proxy Approachesmentioning
confidence: 99%